CHARACTERISTICS OF MINERAL ALTERATION ZONES IN KADIDIA GEOTHERMAL FIELD, SIGI DISTRICT, CENTRAL SULAWESI PROVINCE - Rachmatika, Danella; Haryanto, Agus Didit; Hutabarat, Johanes; Hermawan, Dudi; Mustofa, Santia Ardi (Journal of Geological Sciences and Applied Geology, 2019)
Kadidia geothermal area is located in Sigi Regency, Central Sulawesi Province. The survey area is about 57.1 km from the city of Palu and about 41.9 km from the capital city of Sigi Regency, Sigi Biromaru. The purpose of this research is to determine the characteristics of hydrothermal alteration in the research well. The method used is petrological analysis on KDD-1 well core data starting from the depth of 44,3 m – 703,85 m, petrographic analysis on 17 rock samples and Specterra analysis based on secondary data. The alteration minerals that appeared in research wells include chlorite, calcite, sericite, secondary quartz, iron oxide, opaque minerals and clay minerals with alteration types in the form of replacement and direct depositional. Based on the presence of minerals and determination of alteration zones, obtained Chlorite-Calcite-Illite-Smectite zone, which is characterized by the presence of chlorite, calcite, smectite, sericite alteration minerals at a depth of ± 12.7 m to ± 599 m. At depth of ± 599 to ± 703 m, alteration minerals that appear include chlorite, calcite, illite-smectite which are more dominant. Furthermore, it also found the presence of secondary quartz minerals that fill vugs, sericite and iron oxides with a rare intensity. This zone includes in the argillic zone with a temperature of 140°C - 220°C. It was concluded that the alteration rocks in KDD-1 wells are estimated as caprock zones of the Geothermal Kadidia system, which are formed because of the interaction between rocks and acidic fluid to low acid.